DICTION ON MEDIA INDONESIA EDITORIALS - Vita Kumala Sari; Ani Rakhmawati; Chafit Ulya; Nguyen Thanh Tuan (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
Journalistic language is language that saves words and sentences. Although thrifty, no means language journalism can against grammar applicable standard. Word choice or correct dictionÂ Â  in language journalism is urgently needed in write something news or editorial. The more lots existing vocabulary a journalist so the better writing is also produced. Objective study is to describe the diction used in the editorial of Media Indonesia. This study manifold study description qualitative with approach analysis contents. The result show that the editorial team of Media Indonesia using synonymous words, sense value words, abstract words, concrete words, general words, special words, straightforward words, and borrowed words in the writing.